Outcome of major abdominal surgeries in COVID-19 positive patients with awake anaesthesia: surgeons’ perspective - Thakuria, Kailash K.; M., Naveen Kumar; Boro, Monmohan (International Surgery Journal, 2021)
In view of the COVID-19 pandemic, the use of locoregional anaesthesia has gained popularity as the greatest number of the major abdominal surgical cases which were usually done under general anaesthesia (GA) is now shifted towards awake anaesthesia due to fear of aerosol generation. In a COVID era, with evolving risk of aerosol generation in surgery under GA and the urge for reserving ICU beds for needy patients, this study was undertaken to assess the adequacy of surgery and other benefits with awake anaesthesia. A retrospective observational study for 8 COVID-19 positive patients, undergoing emergency major abdominal surgeries with locoregional anaesthesia in pre-operatively diagnosed COVID positive from May 2020 to May 2021 was conducted. Low to medium risk patients (ASA 1-2) were considered following assessment by anaesthesiologist. We retrospectively analysed data including perioperative events, post-op follow up. The mean operative time was 103 minutes (minimum 50 minutes; maximum 170 minutes). In one case, conversion to general anaesthesia was necessary. Post-operative pain was always well controlled. None of them required postoperative intensive care support. No perioperative major complications (Clavien Dindo ≥3) occurred. Early readmission after surgery never occurred. In our experience in the COVID-19 era, RA may help to limit the intubation-related risk of contagions inside theatres and could be feasible, safe, and painless alternative to GA in selected cases and this approach could become part of an ICU-preserving strategy.